ОБ'ЄКТИ ГЕОТУРИЗМУ ЧЕРНІВЕЦЬКОЇ ОБЛАСТІ У ТРАНСКОРДОННИХ МАРШРУТАХ БУКОВИНОЮ - Бучко, Жанна Іванівна (Львів: НВФ «Карти і атласи», 2016)
The goal of this paper is to study the prospects of establishing and supporting geotourist routes at the trans-boundary territory of Chernivtsi region in Ukraine. We describe 58 objects for geotourism: geological, karst-caving sights of nature and wildlife preserves.
GEOTOURIST OBJECTS OF CHERNIVTSI REGION IN CROSS-BORDER ROUTES BY BUKOVYNA
Keywords: Геотуризм; Транскордонний туризм; Туристичний маршрут; Пам'ятка природи; Заказник